Epidemiology of cardiovascular diseases among patients with diabetes mellitus according to the federal diabetes register of the Russian Federation (2013–2016) - Viktor Y. Kalashnikov (Endocrinology Research Centre, 2019)
BACKGROUND: Cardiovascular diseases (CVD) are the main cause of death for patients with diabetes mellitus (DM). AIMS: To evaluate the CVD epidemiology: coronary heart disease (CHD), myocardial infarction (MI) and cerebrovascular diseases in adult patients with type 1 (T1DM) and type 2 (T2DM) diabetes, compare dynamics with data of implementation of the Federal Program «Diabetes mellitus» in 2007–2012 and over the online period 2013–2016. MATERIALS AND METHODS: The database of the Federal Diabetes register (81 regions at 12.2017). We estimated prevalence and incidence rates/10 thousand (th) adult DM patients over 18 years. RESULTS: The prevalence of CVD for the period 2007 – 2016 significant decreased in CHD for T1DM from 14,9% to 3,5%, for T2DM from 20,1% to 11,7%; MI for T1DM from 5,7% to 1,3%, for T2DM from 7,6% to 3,5%; cerebrovascular diseases for T1DM from 4,9% to 1,7%, for T2DM from 7,6% to 4,3%, respectively. In 2013→2016 positive trends continued: MI for T1DM 8,2→5,9/10th patients, for T2DM 19,2→14,7/10th patients, respectively; CVD for T1DM 11,3→10,5, for T2DM 29,4→25,4/10th patients, respectively. There was a large heterogeneity of the prevalence of CVD in the regions. MI varied in patients for T1DM from 319/10 th patients to absence, for T2DM from 800 to 7/10 th patients; the development of cerebrovascular diseases for T2DM from 900 to less than 100/10 th patients, which is largely due to differences in their registration. A small number of cases may be due to insufficient filling of the database, the facts of a huge number require further analysis. The average age of development of MI had increased: for T1DM 51,2→53 years, for T2DM 63,5→65 years, cerebrovascular diseases for T1DM 52,3→52.5 years, for T2DM 65,2→66,5, respectively. CONCLUSIONS: The prevalence of CVD significantly decreased in the Russian Federation compared to 2007–2012, as well as for the period 2013–2016: the prevalence of CHD and cerebrovascular diseases declined, the number of new cases of MI decreased, the average age and duration of DM before the development of CVD significantly increased. These data reflect the results of the program for improvement medical care and prevention measures for patients with diabetes.